Who Has the Biggest Bulls? Royal Power and the Persepolis Apadāna. Issue 6 (November 2017) - Morgan, Janett
Abstract : Relationships between power and architecture are a feature of all great civilizations and the Achaemenid world was no exception to this. The architecture of Achaemenid buildings and their relief sculpture was designed to reflect and reinforce the power and status of the Great King. At the heart of this visual program lay the audience hall (apadāna) at Persepolis. In seeking to explain and understand the messages written into this building, we tend to approach the structure as a completed work and view it from the last point in its lifecycle. As a result, we focus on its tribute procession relief and allow ideas of empire to dominate our gaze. This limits our ability to understand how and why the building's intended audience and message of power might have diverged at different stages in its construction. This article re-examines the art and architecture of the audience hall at Persepolis and redirects the viewer's gaze to the images of bulls rather than the tribute procession. In focusing on the role of bulls in the scheme of decoration, the article presents a more nuanced reading of the building in its historical, social and architectural context. It shows how Darius I used the Persepolis apadāna to display his authority to rule and to assert the primacy of his status amongst his fellow elites.